IPTEKS FAKTOR – FAKTOR PENGHAMBAT PROSES PELAPORAN DATA SISTEM INFORMASI RUMAH SAKIT (SIRS) BERBASIS ONLINE PADA RSUP PROF. DR. R. D. KANDOU MANADO - Taroreh, Lyviani; Kalalo, Meily Y.B. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
According to Permenkes Republic of Indonesia Number 1171 / MENKES / PER / VI / 2011 concerning SIRS that every hospital is required to implement an online hospital information system to improve the quality of services to hospitals. But in this case there are things that hinder the online SIRS reporting process, namely: (1) The internet network is often disrupted, (2) Lack of knowledge about SIRS. The author recommends RSUP Prof. Dr. R.D. Kandou Manado to facilitate more internet connections so that the reporting process is not inconvenient and easier and socializes the importance of Hospital Information Systems to improve the quality of hospital services.Keywords: Reporting, Hospital Information Systems, Internet Networks, Human Resources